Romania : Technical Assistance Report- Improving Compliance Risk Management of Large Taxpayers. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Technical Assistance report discusses measures for improving compliance risk management of large taxpayers in Romania. The Large Taxpayer Office (LTO) Risk Management Unit needs appropriately skilled staff and good analytic facilities to identify and mitigate risks. The existing structure has too many people reporting directly to the LTO Director General. The changes in staff following restructuring will present an opportunity to renew and enhance LTO staff capabilities to better support modern risk-based methods. The risk decision making and transparency in the LTO also need to be improved to support compliance management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet